Reconstruction of the Role of a Family Member by Prisoners Involved in Hospice Volunteering - Deka, Renata (Paedagogia Christiana, 2021)
Man as a social being needs other people to be able to function and fulfill himself in various social roles. The family is the primary environment, allowing its members for development and satisfying needs. The aim of the article is to present how convicts engaged in hospice volunteering reconstruct their role as a family member. In the following parts, the issues concerning the importance of the family in the lives of persons deprived of liberty, the founding of the hospice volunteering program and the most important results of the conducted own research will be presented. The analysis show that the family is a key value for the inmates, and volunteers take actions aimed at changing their own image in the eyes of their loved ones.